(untitled) (Journal of the College of Basic Education, 2024)
The research aims to identify the impact of the six-dimensional strategy on the development of literary skills among fifth grade literary students. To achieve the goal of the research, the researcher formulated the following two zero hypotheses: 1- There is no statistically significant difference at the level of significance (0,05) between the mean scores of students of the experimental group who study literature using the six-dimensional strategy and the mean scores of students of the control group who study literature in the traditional way in developing literary skills. 2- There is no statistically significant difference at the level of significance (0,05) between the mean scores of the experimental group students in developing literary skills in the pre and post choices. The research sample consisted of (60) students in (Ali bin Abi Talib Preparatory School) affiliated to the General Directorate of Education in Diyala Governorate / Muqdadiya Education Department (Center), divided into two divisions and each division (30) students. The researcher rewarded the students of the two groups in the following variables: The scores of the Arabic language subject in the final exam for the previous academic year (2020/2021), the chronological age of students calculated in months, the academic achievement of fathers, the academic achievement of mothers, and the pre-literary skills tests. The scientific subject was identified with the five subjects from the Arabic language book, which are to be taught to fifth grade literary students in the second semester of the academic year (2021/2022). The researcher formulated behavioral goals and prepared teaching plans. The researcher used the partial experimental method in designing the research. Then the researcher prepared a test between the pre-test and the post-achievement test to measure literary skills. The experiment was applied for an entire semester, which is the second semester of the academic year (2021/2022). The researcher used a number of statistical methods for the updated statistical program (SPSS), the nineteenth edition After analyzing the data, the research showed the following results: The students of the experimental group who study literature using the six-dimensional strategy outperformed the students of the control group who study literature using the traditional method. There is a difference between the mean scores of the students of the experimental group in the development of literary skills in the pre and post tests and in favor of the post test. In the light of the results, the researcher drew conclusions, including: The possibility of applying the six-dimensional strategy in teaching literature in the fifth literary class, because of its active role in the educational process. The use of traditional methods in teaching literature is no longer effective in the educational process, and modern strategies must be used as required by modern education and its advanced technologies. The researcher made a number of recommendations, including: The need to use modern strategies, including the six-dimensional strategy, in teaching literature in the fifth literary class, because of its great role in achieving the teaching objectives of this subject. The need to train teachers and prepare them to teach according to modern strategies, including the six-dimensional strategy for use in teaching literature in the fifth literary class. The researcher suggested a number of proposals, including: Conducting a study similar to this research in other academic stages. Conducting a study similar to this study to identify the impact of the six-dimensional strategy on other dependent variables such as: creative thinking, , in other stages and subjects.